Hubungan Hemoglobin Terglikasi (Hba1c) dan Triglyceride To Hdl-C Ratio (Tg/Hdl-C) Pasien Diabetes Mellitus Tipe 2 Peserta Prolanis di Kabupaten Purbalingga - Dita Panve Songga; Anis Kusumawati; Mustika Ratnaningsih Purbowati; Yusuf Adi Gunawan (Jurnal Anestesi, 2026)
Type 2 diabetes mellitus is a chronic metabolic disease often accompanied by dyslipidemia, which increases the risk of cardiovascular complications. Glycated hemoglobin (HbA1c) reflects long-term glycemic control, while the ratio TG/HDL-C is an indicator of atherogenic dyslipidemia. To determine the association between HbA1c levels and the TG/HDL- C ratio among patients with type 2 diabetes mellitus participating in Prolanis in Purbalingga Regency. This study used an observational analytic design with a cross-sectional approach. A total of 138 patients with type 2 diabetes mellitus participating in the Prolanis program at Purbalingga, Kaligondang, and Kejobong Primary Health Centers. Data on HbA1c, triglyceride, and HDL-C levels were obtained from medical records. The association between variables was analyzed using Spearman’s correlation test. The majority of patients were female, aged 60–69 years with predominantly uncontrolled glycemic status and relatively high TG/HDL-C ratios.